PELAKSANAAN PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DI KABUPATEN KEPULAUAN MERANTI TAHUN 2017 - Nurtanza, Rachmad; ", Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Taxes are taxes payable by any motor vehicle owner who drives their vehicle on a public road. The interest of taxpayers in paying taxes is an obligation. This is because taxes are useful, one of them is for the stability of the country's infrastructure and economic development. The wording of the problem being adopted is how the implementation of the motor vehicle tax by the Meranti Islands Regency Regional Tax Office in 2017 and what are the inhibiting factors in optimizing the motor vehicle tax revenues in Kepulauan Meranti Regency, province Riau in 2017.The purpose of this study is the first to describe the form of implementation carried out by the regional income of the UPT in motor vehicle tax income in Meranti Islands Regency, Riau province in 2017. The second is to determine the inhibiting factors in optimizing the income from motor vehicle tax. in Kepulauan Merant Regency, Riau Province 2017. The research method used is qualitative research. This type of research is descriptively qualitative. The location of this investigation is in the Regional Revenue Unit of the Meranti Islands Regency. Techniques for data collection through interviews and documentation. Data analysis techniques through data reduction, data presentation and data verification.The results of the study show that in the implementation of the motor vehicle tax by the Meranti Islands Regional Tax Authority in 2017, a series of activities takes place, including calculating tax object and taxpayer data, determining the amount of the tax tax, collecting taxes. and supervision of deposits. The inhibiting factors in the collection of motor vehicle tax by the Meranti Islands regency regional tax authority in 2017 are inadequate facilities and infrastructure, low human resources, low community participation, inadequate budget for activities, geographic conditions in the Meranti Islands regency and the lack of coordination between the Riau Provincial Bapenda and the Regional Revenue Unit of the Meranti Islands regency. Keywords: Object data and tax subjects, tax amount, tax collection, supervision.